The islands in the formation of the Continental Platforms - Graça, P. (Transatlantic Studies Association 19 Annual Conference Centre for International Studies, ISCTE-IUL, Lisbon 5-7 July 2021, 2021)
Panel Islands and Transatlantic Relations, Transatlantic Studies Association 19 Annual Conference, Centre for International Studies, ISCTE-IUL, Lisbon, Portugal, 5-7 Julho 2021 The legal concept of “island” has changed over the years, essentially within the framework of the various Conferences on the Law of the Sea that took place. However, it was from the Declaration of the American President Harry Truman on the Continental Shelf of 28 September 1945, that we were aware that such islands, whatever their size, could generate very vast maritime spaces, often far superior to their own physical dimension. This awareness led to the emergence of in-depth studies on the notion of an island, testing criteria and theories about this figure. The 1982 United Nations Convention on the Law of the Sea, which created the 200 nautical miles exclusive economic zone, did also establish continental shelf rights for States with physical continental shelves (platforms) that extend beyond that distance. The reality is that we face a legal definition of a continental shelf that differs significantly from the geological definition. This situation has special interest in States with islands. Concerning Portugal, the country presented in May 2009 to the UN Commission for the Continental Platform Enlargement Limits the Portuguese Project, proposal that was developed with the purpose to sustain the national sovereignty enlargement over the marine seabed and subsoil, besides the 200 maritime miles towards a possible area of 4 million sq.km. This project, with the very important role of the two Portuguese archipelagic islands of Azores and Madeira, brings huge economic opportunities linked to the mineral, energy and genetic resources exploitation, but also the possibility of a new central role of the country as an Atlantic State.